Attitude Control System for InnoSAT - Anon (Universiti Malaysia Perlis, 2009)
To develop attitude control algorithms software; ACS is the part of the ADCS payload. The ACS has Adaptive Predictive Fuzzy Logic. The objective of this project is to develop attitude control algorithms that are going to be tested when the InnoSAT is in the orbit. Upon deployment in the near Equitorial Orbit (NEqO), it will tumble and has difficulty to oriented itself. Hence the needs to control the designated orientation. This is called Attitude Control System (ACS). On receiving the desired and actual angles, intelligent control algorithms using the Adaptive Predective Fuzzy Logic Control (APFLC) and Adaptive Parametric Black Box (APBB) will be employed separately according to the command sequence that will be determined by the InnoSAT's main controller. Resulted data from this control algorithm experiments will be downlink to the ground contro for analysis.